PERLINDUNGAN HUKUM TERHADAP ANAK DISABILITAS FISIK AKIBAT PERUNDUNGAN - Ratu Rahma, Anisa Fadil (Law Jurnal, 2024)
The purpose of this article is to analyze the legal protection of children with mobility disabilities due to bullying in relation to the Disability Act No. 8 of 2016. This review focuses on the rights of people with disabilities and paradigm shifts related to bullying. The research method used in this article is standard legal, using secondary data from information sources such as library materials or written data in the form of books, scientific magazines or encyclopedias of scientific works related to the problem. harassment The law provides a legal basis for the protection of children with physical disabilities and recognizes their rights in various areas of life. This article discusses the legal provisions that apply to people with various disabilities, rights that include self-sufficiency, education, employment, health and more. The application of this law in the context of bullying is analyzed in the light of the special rights of children with disabilities, including the right to be free from neglect, torture, discrimination and abuse. This article also discusses safeguards, legal protection and the role of institutions such as the National Committee for the Disabled. This article details the legal basis and relevant provisions for Indonesia's legislative initiatives to protect children with physical disabilities from bullying. The conclusion reflects the need to further increase awareness, implementation and enforcement of the law to create a safe and inclusive environment for all children without exception